2022
DOI: 10.1101/2022.03.21.485049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The CD58:CD2 axis is co-regulated with PD-L1 via CMTM6 and governs anti-tumor immunity

Abstract: The cell autonomous balance of immune-inhibitory and -stimulatory signals is a critical yet poorly understood process in cancer immune evasion. Using patient-derived co-culture models and humanized mouse models, we show that an intact CD58:CD2 interaction is necessary for anti-tumor immunity. Defects in this axis lead to multi-faceted immune evasion through impaired CD2-dependent T cell polyfunctionality, T cell exclusion, impaired intra-tumoral proliferation, and concurrent protein stabilization of PD-L1. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…While studies in mice suggested a modest role for CD2 ( 29 , 58 ), it is clearly important in human T cell function ( 32 , 59 ), including elimination of cancerous ( 60 , 61 ) and virus-infected ( 62 ) cells. Defects in CD58 (either loss of expression or mutations) have been reported in B cell and T cell lymphomas ( 63 – 65 ), and CD2 expression on tumor-infiltrating T cells has been shown to correlate with their function in several cancers ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…While studies in mice suggested a modest role for CD2 ( 29 , 58 ), it is clearly important in human T cell function ( 32 , 59 ), including elimination of cancerous ( 60 , 61 ) and virus-infected ( 62 ) cells. Defects in CD58 (either loss of expression or mutations) have been reported in B cell and T cell lymphomas ( 63 – 65 ), and CD2 expression on tumor-infiltrating T cells has been shown to correlate with their function in several cancers ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the CD58-CD2 axis can lead to immune evasion not only through lack of T-cell costimulation through CD2, but also through increased inhibition of T cells through PD-L1/PD 1 signaling. 53 CD58 mutations lead to decreased CD58 mRNA expression and are associated with poor response to CAR T-cell therapy, but could represent a genetic marker for CD2 costimulation approaches. 54 As CD58 is coregulated by PD-L1, it will be of major interest to investigate whether incorporation of checkpoint inhibition to the frontline treatment can overcome the various genetic immune escape mechanisms present in PMBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a research laboratory's experience performing multimodal high-resolution, single-cell and single nucleus sequencing coupled with spatial transcriptomics and whole-genome sequencing on trace amounts of archived tumor tissues (Anderson et al, 2022;Biermann et al, 2022), including melanoma (Wang et al, 2023), was discussed.…”
Section: Ba S Ic and Tr Ans L Ational Scientifi C Effortsmentioning
confidence: 99%